Awareness of Performance on a Functional Cognitive Performance-Based Assessment Across the Adult Lifespan - Arora, Catherine; Frantz, Carina; Toglia, Joan (Frontiers in Psychology, 2021)
As people age, their cognitive skills and ability to complete complex instrumental activities of daily living often declines in subtle ways. Older adults who are aware of these slight cognitive and functional changes spontaneously adapt and implement strategies to maximize performance. On the other hand, older adults with limited self-awareness are less likely to adjust performance or initiate compensatory strategies as they may not recognize the need to do so. This places them at higher risk of functional decline and loss of independence. Research on awareness of functional performance in healthy adults is, however, limited and there is a paucity of assessment tools available to address questions of awareness and strategy use in functional tasks. We used the Weekly Calendar Planning Activity (WCPA) – a performance-based assessment of functional cognition including measures of awareness and strategy use – to investigate differences in performance, awareness, and strategy use across the adult lifespan. The WCPA requires examinees to schedule appointments into a weekly calendar while following rules designed to increase task demands. Healthy adults (n=342) from ages 18-92 were observed for strategy use and error recognition while a post-test interview probed participant’s reported strategy use and estimation of accuracy. The discrepancy between participant estimation and actual accuracy provided a measure of online awareness of performance where a larger estimation discrepancy indicated over-estimation of performance. Performance on the WCPA declined across the adult lifespan. Older adults were less likely to use self-monitoring strategies and used less effective strategies overall. Overestimation was associated with use of fewer strategies and lower accuracy in all age groups. Importantly, twice as many older adults overestimated compared to younger adults. Furthermore, the subset of older adults who had good awareness of performance were more likely to use effective strategies, to recognize errors, and achieved accuracy on par with their younger counterparts. Our results emphasize the importance of examining self-awareness of performance and analyzing the strategies used to perform a complex functional task. This information provides a foundation for early detection of functional decline in aging and for designing interventions to maximize functional independence in aging.